1985
DOI: 10.1177/0310057x8501300406
|View full text |Cite
|
Sign up to set email alerts
|

Patient Comfort and Plasma Lignocaine Concentrations during Fibreoptic Bronchoscopy

Abstract: In a preliminary prospective study, eleven outpatients undergoing fibreoptic bronchoscopy using a titrated dose of topical lignocaine anaesthesia were studied. Patient comfort, lignocaine dosage and resultant plasma concentrations were measured at four stages during the procedure. Large total doses, mean 512 (SD 55) mg lignocaine, were frequent and systemic absorption was unpredictable with two patients having plasma concentrations in the toxic range (>5JAg/ml). Peak plasma concentrations, mean 2.3 (SD 1.4) JA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Two millilitre (40 mg) of 2% lignocaine (fixed volume) was used, which is considerably less than the amount of lignocaine used in a study by Sutherland et al [7], in 1985, in which a fixed dose of 370 mg of lignocaine was used to topically anaesthetize the airway for fibre optic bronchoscopy and no incidence of toxic plasma concentrations of lignocaine was recorded. We found that there was a gradual rise in intracuff pressure from 15 min after cuff inflation.…”
Section: Discussionmentioning
confidence: 99%
“…Two millilitre (40 mg) of 2% lignocaine (fixed volume) was used, which is considerably less than the amount of lignocaine used in a study by Sutherland et al [7], in 1985, in which a fixed dose of 370 mg of lignocaine was used to topically anaesthetize the airway for fibre optic bronchoscopy and no incidence of toxic plasma concentrations of lignocaine was recorded. We found that there was a gradual rise in intracuff pressure from 15 min after cuff inflation.…”
Section: Discussionmentioning
confidence: 99%
“…Up to this concentration topical lignocaine generally is safe, hypersensitivity reactions rare, clinically significant bronchoconstriction does not occur and toxic plasma levels are not reached 25 . A total topically administered dose of greater than 512 mg has been shown to have the potential of causing toxic serum concentrations 32 . It is recommended that when administering topical lignocaine the total dose be calculated cumulatively to avoid giving potentially toxic doses.…”
Section: Anaesthesia/sedationmentioning
confidence: 99%
“…25 A total topically administered dose of greater than 512 mg has been shown to have the potential of causing toxic serum concentrations. 32 It is recommended that when administering topical lignocaine the total dose be calculated cumulatively to avoid giving potentially toxic doses. The total dose should be recorded as part of the written report, together with all other drugs administered.…”
Section: Sedative Antagonist Drugsmentioning
confidence: 99%
“…Although topical anesthetics are rapidly absorbed into the circulation after administration onto mucous membranes, raising the possibility of systemic adverse events, 15 blood lidocaine levels after the administration of nebulized lidocaine at normal doses seem low in adults. 16 In an RCT evaluating nebulized lidocaine as an anesthetic for flexible bronchoscopy in children, 17 doses of 4 and 8 mg/kg of 2% lidocaine were well tolerated, with no adverse effects or signs or symptoms of lidocaine toxicity. Blood lidocaine levels were well below toxic levels.…”
mentioning
confidence: 98%